Tingkat Pemahaman Siswa Terhadap Pembelajaran PJOK Menggunakan Media Youtube di SMKN 1 Klari - Kurnia, Rafky Helri (Jurnal Literasi Olahraga, 2022)
This study aims to find out how high the level of understanding of class XI students is on physical education, sports and health through youtube media at SMKN 1 Klari. This research is quantitative descriptive. The method used in this study is a survey method with an instrument in the form of multiple choice questions. The subjects in this study were students of SMKN 1 Klari, Karawang Regency, amounting to 72 people. The data analysis technique in this study used quantitative descriptive analysis presented in the form of percentages. The results of this study indicate that the level of understanding of class XI students on the material for physical education, sports, health and developer activities in PJOK subjects through youtube media at SMKN 1 Klari, Karawang Regency is in the "very low" category of 1.37% (1 student) , “low” was 19.18% (14 students), “high” was 71.23% (52 students), and “very high” was 8.22% (6 students). Based on the average value, which is 60.00, the level of knowledge of class XI students at SMKN 1 Klari, Karawang Regency is high.